Human resource development in Asia – thriving on dynamism & change: reflections from 2006 Asian HRD conference - Ismail, Maimunah; Osman-Gani, Aahad M.; Ahmad, Shamsuddin; Krauss, Steven Eric; Ismail, Ismi Arif; Mohd Hajaraih, Syahidatul Khafizah (Routledge, 2007)
This article discusses the experiences of the conference management team and the host (Universiti Putra Malaysia -UPM) of the Fifth Asian Conference of the Academy of Human Resource Development, held in Putrajaya, Malaysia from 2 to 5 December 2006. In reviewing the conference, the following sub-topics are used for organizing the contents of the article: HRD in Malaysia; conference theme & overview; participations/country representations and paper streams; keynote addresses; conference assessment; and conclusions. At the end, brief perspectives of the next Asian HRD conference to be held in China are also provided.